Aphid–parasitoid diversity in urban green areas: a background for conservative control strategies. Issue 3 (2nd October 2018) - Pons, X.; Lumbierres, B.; Madeira, F.; Starý, P.
ABSTRACT: Plant–aphid–parasitoid associations in urban green areas of the north-eastern Iberian Peninsula were analysed to identify the diversity of aphid parasitoid species, their trophic relationships and to improve the results of biological control efforts. In 245 tritrophic plant–aphid–parasitoid associations, 33 Aphidiinae species belonging to 13 genera were identified. Only two species, Pseudopraon mindariphagum and Trioxys phyllaphidis, can be considered to be monophagous. Most of the species were narrow, moderate or broad oligophagous but an as-native species, Lysiphlebus testaceipes, was recorded to be associated with 39 aphid species and with seven subfamilies/tribes of aphids in 81 tritrophic associations. The potential role of L. testaceipes and other native and commercialised parasitoid species is discussed. Our results point out that the conservation and enhancement of the both native and as-native local parasitoids is crucial for an aphid biological control strategy in urban green areas.